Unusual Necrotizing Uterine Adenocarcinoma in a Dog - Tae-Jung Kim; Sung-Shik Shin; Sang-Ik Park (The Korean Society of Animal Reproduction and Biotechnology, 2017)
A 2-year-old female Maltese dog was admitted with a history of pyometra and resulting peritonitis and septicemia. Uterine specimen sampled by ovariohysterectomy was processed routinely for histopathological observation. Grossly, the uterine mucosa was covered with necrotic debris and on the cut surface, lesion extended into the uterine wall. Microscopically, severe necrosis was observed throughout thickened mucosa, submucosa, and wall of uterus. Tumorous lesions composed of anaplastic cells with bizarre nuclei or tubular structures of cuboidal to short columnar cells were infrequently observed around the necrotic lesions and muscular layer far from necrotic areas. Immunohistochemically, central necrotic area with ambiguous cell and tissue structures, peri-necrotic tumor lesions, and muscular layer were strongly positive for cytokeratin. Since huge necrosis of adenocarcinoma lesions in this case made it difficult to diagnose, immunohistochemical results enable to diagnose as a severe necrotizing adenocarcinoma. Thus, histopathological and immunohistochemical findings in this case may serve as an important knowledge to diagnose uterine adenocarcinoma with huge necrosis in the veterinary field.